Community Empowerment Policy Toward Graha Mina Tourism Model in Natural Resource Management at Kepulauan Seribu - Lilik Sulistyowati (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study aims to analyze community empowerment policy through Graha Mina tourism in naturalresource management at the Kepulauan Seribu group. This study was conducted at Pulau Kelapa and PulauHarapan, Kepulauan Seribu, by using a study case method with a qualitative approach. The result shows:(1). The policy of community empowerment has been conducted as follows: Intensification program offish breeding, community empowerment with captured fishery based, seaweed farming fishery based, cagecultivation fisheries based, tourism and protection based, counseling and training based, and strengtheningcommunity institution based; (2) fisheries based of cage cultivation become a priority program that need tobe applied at Pulau Kelapa and Pulau Harapan. Based on the finding, it was concluded that the community’sunderstanding of natural resource management in the island cluster is still low. Besides, the model andconstruction of Graha Mina marine tourism is a novelty in this research.